Effects of BF2+ implantation on the strain-relaxation of pseudomorphic metastable Ge0.06Si0.94 alloy layers - Oh, MS; Joo, MH; Im, S; Kim, HB; Kim, HK; Song, JH (ELSEVIER SCIENCE BV, 1999)
Metastable pseudomorphic Ge0.06Si0.94 alloy layers grown by molecular beam epitaxy (MBE) on Si (100) substrates were implanted at room temperature by 70 keV BF2+ ions with three different doses of 3x10(13), 1x10(14), and 2.5x10(14) cm(-2). The implanted samples were subsequently annealed at 800 degrees C and 900 degrees C for 30 min in a vacuum tube furnace. Observed by MeV He-4 channeling spectrometry, the sample implanted at a dose of 2.5x10(14) BF2+ cm(-2) is amorphized from surface to a depth of about 90 nm among all as-implanted samples. Crystalline degradation and strain-relaxation of post-annealed Ge0.06Si0.94 samples become pronounced as the dose increases. Only the samples implanted at 3x10(13) cm(-2) do not visibly degrade nor relax during anneal at 800 degrees C. In the leakage current measurements, no serious leakage cm is found in most of the samples except for one which is annealed at 800 degrees C for 30 min after implantation to a dose of 2.5x10(14) cm(-2). It is concluded that such a low dose of 3x10(13) BF2+ cm(-2) can be doped by implantation to conserve intrinsic strain of the pseudomorphic GeSi, while for high dose regime to meet the strain-relaxation, annealing at high temperatures over 900 degrees C is necessary to prevent serious leakages from occuring near relaxed GeSi/Si interfaces. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: SI(100); DEFECTS; SILICON